2002
DOI: 10.1093/glycob/cwf069
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of the putative heparan sulfate-binding motif BBXB of RANTES to transendothelial migration

Abstract: The chemokines are a family of small chemoattractant proteins that have a range of functions, including activation and promotion of vectorial migration of leukocytes. Regulation on activation, normal T cell expressed and secreted (RANTES; CCL5), a member of the CC-chemokine subfamily, has been implicated in a variety of immune responses. In addition to the interaction of CC-chemokines with their cognate cell-surface receptors, it is known that they also bind to glycosaminoglycans (GAGs), including heparan sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…As seen for RANTES (CCL5), apically bound chemokine was sufficient to promote leukocyte migration, although to a smaller extent to that observed under standard assay conditions. 34 These observations are consistent with a recent study that has shown that, at least for lymphocytes, a transendothelial concentration gradient is not necessary for transendothelial migration, with apically bound chemokine providing a sufficient cue. 30 In this study, we demonstrate that MCP-1 is rapidly redistributed from the basal to the apical surface of a model endothelium leaving no evidence of a haptotactic concentration gradient between the cells constituting the monolayer.…”
Section: Competition Of Cell Surface Mcp-1 Binding By Heparinsupporting
confidence: 92%
See 2 more Smart Citations
“…As seen for RANTES (CCL5), apically bound chemokine was sufficient to promote leukocyte migration, although to a smaller extent to that observed under standard assay conditions. 34 These observations are consistent with a recent study that has shown that, at least for lymphocytes, a transendothelial concentration gradient is not necessary for transendothelial migration, with apically bound chemokine providing a sufficient cue. 30 In this study, we demonstrate that MCP-1 is rapidly redistributed from the basal to the apical surface of a model endothelium leaving no evidence of a haptotactic concentration gradient between the cells constituting the monolayer.…”
Section: Competition Of Cell Surface Mcp-1 Binding By Heparinsupporting
confidence: 92%
“…in serum-free DMEM was applied to an EA.hy926 monolayer for 1 h at 371C. 34 Monolayers were then washed twice for 5 min in serum free DMEM at room temperature prior to transfer to the standard migration assay system. Migration was for 90 min at 371C to allow direct comparison to the standard assay described above.…”
Section: Apical Application Of Chemokinementioning
confidence: 99%
See 1 more Smart Citation
“…These gradients can provide the motivation for vectorial cell migration, resulting in selective recruitment of leukocytes from the subendothelial to the tubular compartments. This model was recently supported by data from our group showing that a mutant variant of RANTES with a reduced potential to bind heparan sulphate but normal affinity for the specific chemokine receptor CCR5 induced a smaller chemotactic response than the wild-type chemokine (33).…”
Section: Post-transplant Renal Tubulitismentioning
confidence: 68%
“…This interaction has a number of important functions, including protection, concentration and presentation of cytokines which are produced in small quantities by a small number of cells within the microenvironment. This process is believed to be of particular importance for presentation of chemokines on the surface of endothelial cells (Tanaka et al, 1996) and for stabilisation of the concentration gradients necessary for leukocyte chemotaxis (Adams and Lloyd, 1997;Ali et al, 2002;Appay and Rowland-Jones, 2001;Patel et al, 2001;Witt and Lander, 1994).…”
Section: Introductionmentioning
confidence: 99%